Learning with the heart or with the mind: using virtual reality to bring historical experiences to life and arouse empathy. Issue 1 (2nd January 2023) - Richards, Deborah; Lupack, Susan; Bilgin, Ayse Aysin Bombaci; Neil, Bronwen; Porte, Meredith
ABSTRACT: Virtual reality (VR) technology can increase prosocial behaviour toward a target person or group by enhancing their empathic response for the subject, but such technology has not always improved learning outcomes. This interdisciplinary study compared the potential advantages of delivering the same learning material about daily life in an ancient Greek household via two modes of delivery: VR technology and classroom lecture. The VR group explored a Greek villa containing historical artefacts and virtual characters with whom they were able to interact through set dialogues. The dialogues illustrated social hierarchies, gender relations, the situation of slaves, cult practice, and religious beliefs. The classroom group received the same information in a classroom environment. Both randomly-assigned groups answered a multiple-choice quiz to evaluate the knowledge gained. They also responded to open-text questions designed to test the degree of empathy that was aroused. We found that classroom lecture delivery was significantly superior in terms of the acquisition of factual knowledge, consistent with cognitive learning theory. We identified this as learning with the mind. The immersive VR environment, however, imparted a level of empathic response to the lived experiences of people in ancient Greece; in that sense it allowed learning with the heart.